Nevoid hyperkeratosis of the nipple and/or areola: Treatment with topical steroid - Alireza Ghanadan; Kamran Balighi; Somayeh Khezri; Kambiz Kamyabhesari (Wolters Kluwer Medknow Publications, 2013)
Nevoid hyperkeratosis of the nipple and/or areola (NHNA) is a rare and benign disease, with poorly understood etiology and no definite therapeutic plan. Hereby, we report another case of NHNA, discuss about its clinical and histopathological features, differential diagnosis, and responsiveness to topical steroid.